Association of age with mortality and virological and immunological response to antiretroviral therapy in rural South African adults. - Portia C Mutevedzi; Richard J Lessells; Alison J Rodger; Marie-Louise Newell (PLoS ONE)
Objective To assess whether treatment outcomes vary with age for adults receiving antiretroviral therapy (ART) in a large rural HIV treatment cohort. Design Retrospective cohort analysis using data from a public HIV Treatment & Care Programme. Methods Adults initiating ART 1(st) August 2004-31(st) October 2009 were stratified by age at initiation: young adults (16-24 years) mid-age adults (25-49 years) and older (≥50 years) adults. Kaplan-Meier survival analysis was used to estimate mortality rates and age and person-time stratified Cox regression to determine factors associated with mortality. Changes in CD4 cell counts were quantified using a piecewise linear model based on follow-up CD4 cell counts measured at six-monthly time points. Results 8846 adults were included, 808 (9.1%) young adults; 7119 (80.5%) mid-age adults and 919 (10.4%) older adults, with 997 deaths over 14,778 person-years of follow-up. Adjusting for baseline characteristics, older adults had 32% excess mortality (p = 0.004) compared to those aged 25-49 years. Overall mortality rates (MR) per 100 person-years were 6.18 (95% CI 4.90-7.78); 6.55 (95% CI 6.11-7.02) and 8.69 (95% CI 7.34-10.28) for young, mid-age and older adults respectively. In the first year on ART, for older compared to both young and mid-aged adults, MR per 100 person-years were significantly higher; 0-3 months (MR: 27.1 vs 17.17 and 21.36) and 3-12 months (MR: 9.5 vs 4.02 and 6.02) respectively. CD4 count reconstitution was lower, despite better virological response in the older adults. There were no significant differences in MR after 1 year of ART. Baseline markers of advanced disease were independently associated with very early mortality (0-3 months) whilst immunological and virological responses were associated with mortality after 12 months. Conclusions Early ART initiation and improving clinical care of older adults are required to reduce high early mortality and enhance immunologic recovery, particularly in the initial phases of ART.